Sumber ilmu menurut Ibn Tufayl: Terjemahan dan analisis teks terpilih risalah Hayy Ibn Yaqzan / Nur Rafezza Fetheri - Nur Rafezza , Fetheri (2018)
This study is based on Ibn Ṭufayl’s thought who was an eminent philosopher at the court of al-Muwaḥhidūn of 12th century Andalusia. His thoughts are here deliberated by using the primary text of Risālah Ḥayy ibn Yaqẓān which is the merest work of Ibn Ṭufayl’s survive at the moment. This study entitled “The Sources of Knowledge According to Ibn Ṭufayl: Translation and Analysis of Selected Texts of the Treatise Ḥayy ibn Yaqẓān.” This dissertation examines the background of Ibn Ṭufayl’s writing, the Treatise Ḥayy ibn Yaqẓān and its importance in Islamic epistemological thought. On the other hand, this study also elucidates the sources of knowledge in Ibn Ṭufayl’s thought by focusing the discussion on senses, intellect, intuition and revelation. Apart from that, this study also scrutinizes the influence of the thought of his predecessors: Ibn Sīnā, al-Ghazālī dan Ibn Bājjah in the writing of the Treatise Ḥayy ibn Yaqẓān. This study also provides for the first time an annotated translation from the treatise into Malay of the text. The method employed for information gathering purposes was using a documentation method. In the course of this study, various analysis methods adopted are inductive, deductive, translation and comparative method. The finding indicates that the sources of knowledge in Ibn Ṭufayl’s thought are addressed indirectly in the Treatise Ḥayy ibn Yaqẓān. The reality was, Ibn Ṭufayl’s thought also inspired by Ibn Sīnā, al-Ghazālī and Ibn Bājjah. In fact, Ibn Ṭufayl indebted to al-Ghazālī more than any other scholars, especially in his sources of knowledge theory. Therefore, the discussions of the sources of knowledge are vital to show there are similarities and differences in Ibn Ṭufayl’s thought with them. It also reveals that although there are differences, all of them take the same position in declaring the sources of knowledge refers to the senses, intellect, intuition and revelation. Furthermore, they also related the role of the human soul as the substratum of knowledge. Obviously, the understanding of the epistemological aspect is essential today, especially to acquire the knowledge due to the level of al-‘ilm al-yaqīn. Thus, like any other Muslim scholars contributed in the field of epistemological thought, Ibn Ṭufayl also exposed his best theory of the sources of knowledge in his work the Treatise Ḥayy ibn Yaqẓān.